Prevalence of Prediabetes and Diabetes Mellitus Type II in Bipolar Disorder - Kittel-Schneider, Sarah; Bury, Daniel; Leopold, Karolina; Haack, Sara; Bauer, Michael; Pfeiffer, Steffi; Sauer, Cathrin; Pfennig, Andrea; Völzke, Henry; Grabe, Hans-Jörgen; Reif, Andreas (Frontiers in Psychiatry, 2020)
Introduction: Bipolar disorder (BD) is characterized by recurrent episodes of depression and mania and affects up to 2% of the population worldwide. Patients suffering from bipolar disorder have a reduced life expectancy of up to 10 years. The increased mortality might be due to a higher rate of somatic diseases, especially cardiovascular diseases. There is however also evidence for an increased rate of diabetes mellitus in BD, but the reported prevalence rates vary by large. Material and Methods: 85 bipolar disorder patients were recruited in the framework of the BiDi study (Prevalence and clinical features of patients with Bipolar Disorder at High Risk for Type 2 Diabetes (T2D), at pre-diabetic state and with manifest T2D) in Dresden and Würzburg. T2D and pre-diabetes were diagnosed measuring HBA1c and an oral glucose tolerance test (oGTT), which at present is the gold standard in diagnosing T2D. The BD sample was compared to an age-, sex- and BMI-matched control population (n=850) from the Study of Health in Pomerania cohort (SHIP Trend Cohort). Results: Patients suffering from BD had a T2D prevalence of 7%, which was not significantly different from the control group (6%). Fasting glucose and impaired glucose tolerance were, contrary to our hypothesis, more often pathological in controls than in BD patients. Non-diabetic and diabetic bipolar patients significantly differed in age, BMI, number of depressive episodes and disease duration. Discussion: When controlled for BMI, in our study there was no significantly increased rate of T2D in BD. We thus suggest that overweight and obesity might be mediating the association between BD and diabetes. Underlying causes could be shared risk genes, medication effects and lifestyle factors associated with depressive episodes. As the latter two can be modified, attention should be paid to weight changes in BD by monitoring and taking adequate measures to prevent the alarming loss of life years in BD patients.